2022
DOI: 10.1111/hiv.13257
|View full text |Cite
|
Sign up to set email alerts
|

Re‐valuation of annual cytology using HPV self‐sampling to upgrade prevention (REACH UP): A feasibility study in women living with HIV in the UK

Abstract: Introduction: Current UK guidelines for cervical cancer screening are based on the assumption that most women living with HIV (WLWH) are also high-risk (HR) human papillomavirus (HPV)-positive. We aimed to provide data on prevalence of HR-HPV in WLWH in the UK and to assess feasibility and acceptability of HR-HPV self-sampling in this group.Methods: Women living with HIV attending six HIV services in London/south of England, with no history of cervical cancer, were enrolled. Participants selfcollected a vagina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Accumulating evidence has provided strong and consistent data that HPV persistence is the main factor influencing the risk of developing HPV-related disease, including cervical dysplasia and cervical cancer (Casarin et al ., 2020; Falcaro et al ., 2021; Mix et al ., 2022; Di Donato et al ., 2023; Giannini et al ., 2023). Duration of HPV persistence, viral load, deregulation of HPV gene expression, and host epigenetic mechanisms (including methylation of imprinted gene control) are the main factor influencing the process of tissue transformation (Smith et al ., 2022; Cicconi et al ., 2022; Demarco et al ., 2022; Mix et al ., 2022). Although a high level of evidence highlighted that HPV persistence correlates with the risk of developing either primary or recurrent cervical dysplasia, no evidence regarding the impact of duration of HPV infection is still available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence has provided strong and consistent data that HPV persistence is the main factor influencing the risk of developing HPV-related disease, including cervical dysplasia and cervical cancer (Casarin et al ., 2020; Falcaro et al ., 2021; Mix et al ., 2022; Di Donato et al ., 2023; Giannini et al ., 2023). Duration of HPV persistence, viral load, deregulation of HPV gene expression, and host epigenetic mechanisms (including methylation of imprinted gene control) are the main factor influencing the process of tissue transformation (Smith et al ., 2022; Cicconi et al ., 2022; Demarco et al ., 2022; Mix et al ., 2022). Although a high level of evidence highlighted that HPV persistence correlates with the risk of developing either primary or recurrent cervical dysplasia, no evidence regarding the impact of duration of HPV infection is still available.…”
Section: Discussionmentioning
confidence: 99%
“…The role of HPV in determining the occurrence of cervical dysplasia and cervical cancer is well established (Falcaro et al, 2021;Bukowski et al, 2022;Demarco et al, 2022;Mix et al, 2022;Smith et al, 2022). More interestingly, HPV persistence, as well as viral load, are considered two of the main risk factors impacting the risk of cervical dysplasia recurrence (Bogani et al, 2021b;Cicconi et al, 2022;Prétet et al, 2022). Other main risk factors influencing the risk of cervical dysplasia recurrence include patients' age, positive margin status, and severity of the lesions (Bogani et al, 2019(Bogani et al, , 2020a(Bogani et al, , 2021b.…”
Section: Introductionmentioning
confidence: 99%
“…Only one study [40] mentioned self‐sampling for cervical HPV DNA, yet this method has been approved by the WHO and the ESGO as it has comparable sensitivity to physician‐collected samples and has shown improvement in reaching those who do not routinely attend cervical cancer screening [12, 13, 38]. Data on HPV self‐sampling among WLWH mainly come from outside Europe [41], and therefore Cicconi et al's finding that WLWH in England found self‐sampling acceptable is of value and could support expanding the use of this method in the WER, particularly for women who decline standard screening [40].…”
Section: Discussionmentioning
confidence: 99%